2015
DOI: 10.1016/j.dnarep.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant and environmental toxicant-induced effects compromise DNA ligation during base excision DNA repair

Abstract: DNA lesions arise from many endogenous and environmental agents, and they promote deleterious events leading to genomic instability and cell death. Base excision repair (BER) is the main DNA repair pathway responsible for repairing single strand breaks, base lesions and abasic sites in mammalian cells. During BER, DNA substrates and repair intermediates are channeled from one step to the next in a sequential fashion so that release of toxic repair intermediates is minimized. This includes handoff of the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 72 publications
1
63
0
Order By: Relevance
“…In the present study, we examined the effects of pol β-mediated oxidized nucleotide insertion on downstream steps in the BER pathway. Our working model for BER suggests that after pol β fills the gap, the resulting nicked BER intermediate is passed to a DNA ligase for completion of repair23. Thus, the effect of oxidized nucleotide insertion on the ligation step is an important topic of investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we examined the effects of pol β-mediated oxidized nucleotide insertion on downstream steps in the BER pathway. Our working model for BER suggests that after pol β fills the gap, the resulting nicked BER intermediate is passed to a DNA ligase for completion of repair23. Thus, the effect of oxidized nucleotide insertion on the ligation step is an important topic of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…There is channelling of the repair intermediate after pol β nucleotide insertion to the final step in BER, DNA ligation, where a DNA ligase catalyzes phosphodiester bond formation between 3′-OH and 5′-P groups of the nicked BER intermediate2021. Since DNA ligase activity requires a natural annealed base pair at the 3′-margin of the nick22, mismatched or oxidized nucleotide insertion during the gap-filling step could result in disruption of BER23. However, the potential effect of oxidized base insertion on DNA ligation is not well understood.…”
mentioning
confidence: 99%
“…It has been found that coordination between these BER enzymes is crucial and, when deficient, is associated with loss of cell viability and genomic stability [17, 19]. However, the mechanism of how unrepaired single-strand break intermediates are generated during the repair of endogenously and environmentally induced cytotoxic and mutagenic lesions is still under investigation [20, 21]. Left unrepaired, these blocked ends could interrupt BER, block replication and transcription, and be converted into toxic double-stranded breaks.…”
Section: Introductionmentioning
confidence: 99%
“…If pol β were to insert an incorrectly matched or oxidatively damaged nucleotide into the gapped DNA, the resulting nicked product can potentially be passed on to DNA ligase III for nick sealing. However, the presence of the modified or mismatched base pair at the 3′-end of the nick could lead to ligation failure and formation of an abortive ligation product with a 5′-adenylate (5′-AMP) group (8890). Furthermore, if pol β does not remove the 5′-dRP of an AP site using its lyase activity prior to the ligation step, DNA ligases can generate abortive ligation products with a 5′-adenylated dRP containing BER intermediate (78).…”
Section: Further Processing Of the Ap Sitementioning
confidence: 99%
“…This conformational change could possibly disrupt channeling of the substrate from pol β to DNA ligase in the BER pathway and consequently alter the normal coordination during repair. It is also conceivable that the BER intermediate possessing the 5′-AMP group could serve as a signaling mechanism to trigger recruitment of DNA end-processing enzymes (88). After end-processing, pol β would have another opportunity at the gap-filling is inserted, the DNA ligase would ideally be able to successfully join 5′-phosphate and 3′-OH groups to complete the repair.…”
Section: Further Processing Of the Ap Sitementioning
confidence: 99%